A return to mechanical solidarity: panic hoarding and social media in the time of pandemic - Anderson, Patricia (My University, 2020)
The emergence of the Covid-19 pandemic brought many changes to daily life in Canada. One such behavior that surfaced was what could be defined as ‘panic hoarding,’ namely, the purchasing of items such as toilet paper, sanitizer and disinfectant in far greater quantities per person than other times, which risked the creation of shortages across communities. In order to understand such behavior, this article will use ideas from Émile Durkheim to analyze the relationship of social media and its impact on the behavior of panic hoarding. In particular, Durkheim’s concepts of collective consciousness show how social media provides enough impetus to make the case that this pandemic is better defined by mechanical than organic solidarity. We can see social media as the vehicle through which collective consciousness can be experienced, and more immediately so at this time, insofar as we see how it influences panic hoarding behavior. We can also see that social media’s use of memes can be likened to totems, and that they give clues to the values we hold at this time.
Keywords: panic hoarding; social media; COVID-19